Aluminum nitride laminated structure and light emitting device
The AlN laminated structure on a sapphire substrate with controlled protrusions and vapor phase epitaxy addresses irregular growth issues, achieving a flat, pore-free AlN layer that enhances UV-LED performance and reduces costs.
Patent Information
- Application Number
- CN202010086455.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-20
- Filing Date
- 2020-02-11
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2040-02-11
AI Technical Summary
Conventional methods using sapphire substrates with periodically arranged protrusions result in irregular AlN crystal growth with disorderly surfaces and internal voids, which are detrimental for UV-LED applications.
An aluminum nitride laminated structure is developed with a sapphire substrate having periodically arranged protrusions less than 500 nm high, where an AlN layer is grown to form a flat surface with no internal pores, utilizing vapor phase epitaxy and oxygen treatment to enhance crystal orientation and adhesion.
The AlN layer achieves high crystallinity and reduces voids, enhancing light transmission and reducing manufacturing costs, thereby improving UV-LED performance and efficiency.
Smart Images

Figure CN111564539B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an aluminum nitride laminate structure and a light-emitting device. Background Art
[0002] As a method for producing an ultraviolet light emitting diode (LED), for example, a technique for growing an aluminum nitride (AlN) layer on a sapphire substrate having a periodic concave-convex shape is proposed (see, for example, non-patent document 1). As the concave-convex shape of the sapphire substrate, there are known shapes in which concave portions are periodically (and discretely) arranged and shapes in which convex portions are periodically (and discretely) arranged (for a technique for growing an AlN layer on a sapphire substrate having concave portions, see, for example, non-patent document 2).
[0003] Prior art literature
[0004] Non-patent literature
[0005] Non-patent document 1: H. Miyake et al., "HVPE growth of thick AlN on trench-patterned substrate", Phys Status Solidi C 8, No. 5, 1483-1486 (2011)
[0006] Non-patent document 2: L. Zhang et al., “High-quality AlN epitaxy on nano-patternedsapphire substrates prepared by nano-imprint lithography”, Scientific Reports 6, 35934 (2016) Summary of the invention
[0007] Problem that the invention aims to solve
[0008] In the conventional technology, when a sapphire substrate having periodically arranged protrusions is used, irregular and disorderly AlN crystals are grown, and therefore it is impossible to grow an AlN layer with a flat surface.
[0009] In addition, although an AlN layer having a flat surface can be formed by using a sapphire substrate having recesses periodically arranged thereon, this technique forms cavities (holes) inside the AlN layer (see Non-Patent Document 2). As described later, such holes are disadvantageous when the obtained AlN layer is applied to, for example, UV-LEDs.
[0010] An object of the present invention is to provide an AlN stacked structure including an AlN layer grown on a sapphire substrate having periodically arranged protrusions and having a flat surface and substantially containing no voids therein.
[0011] Another object of the present invention is to provide a light-emitting device including such an AlN stacked structure.
[0012] Solutions for solving problems
[0013] According to one embodiment of the present invention, there is provided an aluminum nitride laminated structure comprising:
[0014] A sapphire substrate having a base surface on which projections having a height of 500 nm or less are periodically arranged; and
[0015] The aluminum nitride layer is grown on the aforementioned base surface, has a flat surface, and substantially contains no pores.
[0016] According to another embodiment of the present invention, a light emitting device is provided.
[0017] The device includes the aluminum nitride laminated structure according to the above-mentioned embodiment.
[0018] Effects of the Invention
[0019] Provided is an aluminum nitride stacked structure including an aluminum nitride layer having a flat surface and grown so as to contain substantially no pores inside on a sapphire substrate having periodically arranged protrusions. Also provided is a light emitting device including such an AlN stacked structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 FIG. 1 is a schematic cross-sectional view showing an exemplary embodiment of a stacked structure 100 according to the present invention.
[0021] Figure 2 FIG. 1 is a schematic top view of a substrate 10 according to an embodiment of the present invention.
[0022] Figure 3 The following are AFM images and optical microscope images showing the results of the experimental example.
[0023] Figure 4 : is a cross-sectional SEM image showing the results of the experimental example.
[0024] Figure 5 It is a schematic cross-sectional view of an LED based on an application example.
[0025] Figure 6 FIG. 1 is a schematic plan view of a substrate 10 , illustrating another embodiment in which ridge-shaped protrusions 12 are arranged.
[0026] Figure 7 (a) and Figure 7 (b) is a cross-sectional view schematically showing a processed sapphire substrate used in the conventional technology and an AlN layer grown on the processed sapphire substrate by the conventional technology.
[0027] Description of Reference Numerals
[0028] 10…sapphire substrate, 11…basal surface, 12…convex portion, 13…valley portion, 14…plane, 20…AlN layer, 21…surface, 100…AlN stacked component, 200…LED, 205…light emitting structure, 260…light DETAILED DESCRIPTION
[0029] <One Implementation Method>
[0030] An aluminum nitride (AlN) laminated structure 100 (hereinafter also referred to as the laminated structure 100 ) according to one embodiment of the present invention will be described. Figure 1 1 is an exemplary cross-sectional schematic diagram of a stacked component 100 of the present embodiment. The stacked component 100 includes a sapphire substrate 10 (hereinafter also referred to as substrate 10) and an AlN layer 20 (hereinafter also referred to as layer 20) grown on the substrate 10. The layer 20 of the present embodiment is characterized in that its surface 21 is a flat surface formed by growth and substantially contains no pores inside.
[0031] The substrate 10 is made of single crystal sapphire and has a base surface 11 as a base for growing the layer 20. The base surface 11 has a plurality of protrusions 12 arranged periodically (and discretely). The shape of the protrusion 12 is, for example, conical. In this embodiment, the conical shape includes a cone and a pyramid, and includes not only a shape with a sharp top but also a shape with a flat top (a frustum). Here, an embodiment in which the protrusion 12 is conical is exemplified.
[0032] The outer portion 13 of the basal surface 11 (hereinafter also referred to as the valley 13) of the convex portion 12 is arranged on a (virtual) plane 14. It can be considered that the convex portion 12 is arranged on the plane 14, and the normal direction N14 of the plane 14 is the height direction of the convex portion 12. The height H12 of the convex portion 12 is specified by the distance from the plane 14 to the upper end of the convex portion 12. The convex portion 12 is formed in a manner that the height direction of the convex portion 12 is parallel to the c-axis direction of the sapphire constituting the substrate 10. The top of each convex portion 12 exposes the c-plane of the sapphire. It should be noted that in this specification, "a certain direction D1 is parallel to another direction D2" means that the angle formed by a certain direction D1 and another direction D2 is less than 3°.
[0033] Figure 21 is an illustrative top view of the substrate 10. In the present embodiment, the protrusions 12 are periodically (and discretely) arranged in two dimensions by, for example, being arranged at the grid points of a triangular grid, a quadrangular grid or a hexagonal grid. Here, an embodiment in which the protrusions 12 are arranged at the grid points of an equilateral triangular grid is illustrated. The axial direction of the equilateral triangular grid is indicated by a single dotted line. The axial direction of the triangular grid or the like in which the protrusions 12 are arranged is not particularly limited, and may be, for example, parallel to the m-axis direction or the a-axis direction of the sapphire constituting the substrate 10.
[0034] The layer 20 is composed of AlN grown heteroepitaxially on the base surface 11 of the substrate 10. The surface (upper surface) 21 of the layer 20 is a flat surface formed by growth. Here, the surface 21 is a flat surface (or flat) means that the surface 21 has a surface roughness of typically less than 3 nm in terms of the root mean square value (RMS) measured by an atomic force microscope (AFM) through a 5 μm square area. The base surface 11 of the substrate 10 has a concave-convex shape corresponding to the protrusion 12, and the surface 21 of the layer 20 is flat. That is, the surface 21, which is a flat surface, is formed by growing the layer 20 to fill the valley 13 of the base surface 11.
[0035] The layer 20 contains substantially no pores inside. That is, the layer 20 completely fills the valleys 13 between the protrusions 12. The definition of "the layer 20 contains substantially no pores" will be described later.
[0036] The AlN constituting layer 20 controls the crystal orientation by utilizing the sapphire single crystal exposed on the base surface 11 of the substrate 10, so that the c-axis direction is parallel to the height direction of the protrusion 12. That is, the c-axis direction of the AlN constituting layer 20 is parallel to (roughly consistent with) the c-axis direction of the sapphire constituting the substrate 10. The low-index crystal plane closest to the surface 21 becomes the +c plane (Al polar plane) of the AlN constituting layer 20. The AlN constituting layer 20 is a single crystal, and the surface 21 has a single crystal orientation.
[0037] As described in the experimental examples below (see Figure 3 ), the surface 21 of the layer 20 has a step-terrace structure, and the AlN constituting the layer 20 has high crystallinity. The half width of the AlN constituting the layer 20 measured based on an X-ray rocking curve (XRC) is preferably 300 seconds or less for (0002) diffraction, and is preferably 500 seconds or less for (10-12) diffraction, for example.
[0038] The surface 21 is a flat surface formed by growth (as-grown), not a flat surface flattened by grinding or other processing, so there is no damage to the AlN crystal caused by the processing. Therefore, the surface 21 becomes a surface on which other aluminum nitride layers can be grown in the following manner: when other AlN layers are homoepitaxially grown on the surface 21, the half width of AlN constituting the other AlN layer based on XRC measurement is not more than the same level as the half width of AlN constituting layer 20 based on XRC measurement (that is, the crystallinity is not lower than that of layer 20). "Not more than the same level" means that the half width of the other AlN layer is equal to or less than the half width of layer 20, or even if it increases, the increase is suppressed to less than 100 seconds, that is, the increase in the half width of the other AlN layer is less than 100 seconds compared with the half width of layer 20. Here, the half width is, for example, the half width of (0002) diffraction, or the half width of (10-12) diffraction.
[0039] Layer 20 is composed of a single-layer AlN layer. Here, a "single-layer AlN layer" refers to an AlN layer (hereinafter also referred to as a multi-layer AlN layer) that is not composed of a stack of multiple AlN sub-layers with different concentrations of impurities such as oxygen. In a multi-layer AlN layer, the concentration of impurities such as oxygen changes in a step-like manner at the stacking interface between the AlN sub-layers. Therefore, a "single-layer AlN layer" can be said to be an AlN layer that does not have an interface where the concentration of impurities such as oxygen changes in a step-like manner at a position midway in the thickness direction.
[0040] The inventors of the present application have obtained the following insights: in order to grow the layer 20 in a manner that the surface 21 becomes a flat surface, it is preferable to make the height H12 of the convex portion 12 low. Specifically, the height H12 of the convex portion 12 is preferably 500nm or less, and more preferably 300nm or less. It should be noted that the lower limit of the height H12 of the convex portion 12 is not particularly limited, but from the perspective of clearly defining the convex portion 12, the height H12 of the convex portion 12 is, for example, set to be 50nm or more, preferably 100nm or more.
[0041] As described later, the layer 20 is preferably grown by vapor phase epitaxy, such as hydride vapor phase epitaxy (HVPE), and before the growth of the layer 20, the base surface 11 is subjected to a heat treatment (hereinafter also referred to as oxygen treatment) while being exposed to a gas containing oxygen (O), preferably oxygen (O2 gas). It is believed that by roughening the base surface 11 by the oxygen treatment, the ease of attachment of Al atoms on the entire surface of the base surface 11 is increased, and thus AlN becomes easier to attach in a form consistent with the crystal orientation of sapphire.
[0042] In this embodiment, it is considered that the height H12 of the convex portion 12 is sufficiently low, and the adsorption of Al atoms on the entire surface of the base surface 11 is increased by oxygen treatment, thereby making it easy to fill the valley portion 13. The appropriate growth conditions (growth temperature, V / III ratio, etc.) for growing the layer 20 so that the surface 21 is flat and substantially contains no pores inside will be described later.
[0043] In order to make the surface 21 of the layer 20 a flat surface, the layer 20 is grown to a height (thickness) exceeding the upper end of the protrusion 12. That is, the thickness T20 of the layer 20 from the valley 13 (the lower end of the protrusion 12) to the surface 21 is greater than the height H12 of the protrusion 12. In the present embodiment, by making the height H12 of the protrusion 12 less than 500nm and growing the layer 20 on the oxygen-treated base surface 11, the thickness T20 of the layer 20 from the lower end of the protrusion 12 to the surface 21, which is required to make the surface 21 a flat surface, can be made thin to less than 800nm.
[0044] It can be said that the wider the width W12 of the inclined surface of the convex portion 12 in a plan view, or the wider the pitch P12 between the most adjacent convex portions 12, the greater the degree of the concavity and convexity of the base surface 11, and it can be said that it is more difficult to flatten the surface 21 of the layer 20. As a rough standard of the concavity and convexity of the base surface 11 that can obtain a flat surface 21 by this embodiment, for example, the width W12 is 500nm or less, and another example is that the pitch P12 is 1000nm or less.
[0045] Next, the manufacturing method of the stacked component 100 is described. Prepare the substrate 10. The height H12 of the protrusion 12 of the substrate 10 is set to be less than 500nm. The width W12 of the inclined surface of the protrusion 12 is preferably set to be less than 500nm, and the pitch P12 of the protrusion 12 is preferably set to be less than 1000nm. Such a substrate 10 can be made by the formation technology of a patterned sapphire substrate (PSS). The base surface 11 of the substrate 10 is subjected to oxygen treatment. As an oxygen treatment, for example, it is preferred to perform a heat treatment at a temperature of 800 to 1100°C for 10 to 30 minutes in a tubular furnace where oxygen is circulated at about 2slm. In addition, oxidation of the base surface 11 using oxygen plasma is also a preferred method of oxygen treatment.
[0046] On the oxygen-treated substrate 11, AlN is grown by vapor phase epitaxy, preferably HVPE, to form a layer 20. As the aluminum (Al) raw material gas, for example, aluminum chloride (AlCl) gas or aluminum chloride (AlCl3) gas can be used, and as the nitrogen (N) raw material gas, ammonia (NH3) gas can be used. These raw material gases can be mixed with a carrier gas using hydrogen (H2 gas), nitrogen (N2 gas) or a mixed gas thereof and supplied.
[0047] As growth conditions, the following can be exemplified. As growth temperature, 1000-1300°C can be exemplified. As the supply amount ratio of N raw material gas to Al raw material gas, i.e., V / III ratio, 0.2-200 can be exemplified. As growth rate, 0.5-500nm / minute can be exemplified. It should be noted that in order to prevent AlN from adhering to the nozzle of the gas supply pipe for introducing various gases into the growth chamber of the HVPE device, hydrogen chloride (HCl) gas can also be circulated, and the supply amount of HCl gas can be exemplified as a ratio of 0.1-100 relative to AlCl gas or AlCl3 gas.
[0048] As described above, the layer 20 having a flat surface 21 and substantially no pores inside is grown. The thickness T20 of the layer 20 can be appropriately adjusted as long as it is greater than or equal to the thickness at which the surface 21 becomes a flat surface. However, when the thickness T20 is too thick, there is a concern that cracks may be generated in the layer 20. Therefore, the thickness T20 of the layer 20 is preferably set to 800 nm or less, for example.
[0049] Here, in order to clarify the characteristics of the AlN layer 20 of the present embodiment, the characteristics of the AlN layer grown on a processed sapphire substrate based on the conventional technology are described. The AlN growth on a processed sapphire substrate based on the conventional technology is exemplified in Non-Patent Document 2 and the like. Figure 7 (a) and Figure 7 (b) is a cross-sectional view schematically showing a processed sapphire substrate 310 used in the conventional technology and an AlN layer 320 grown on the processed sapphire substrate 310 by the conventional technology.
[0050] In the conventional technology, in most cases, unlike the present embodiment, a processing substrate of the type in which recesses 312 (holes or grooves) are periodically (discretely) formed on a sapphire substrate 310 is used. The recesses 312 are periodically arranged. Specifically, for example, a structure is used in which recesses 312 are arranged at the grid points of a triangular grid or the like on which the protrusions 12 of the present embodiment are arranged, instead of the protrusions 12 (see Figure 2 ) of the sapphire substrate 310. The intervals between the recesses 312 are as long as approximately 1 μm to several 10 μm, and the depths of the recesses 312 are as deep as approximately 1 μm to several 10 μm. As a method for growing the AlN layer 320, a metal organic chemical vapor deposition (MOCVD) method or a HVPE method can be used.
[0051] In the prior art, the AlN layer 320 is grown with the c-axis perpendicular to each surface on the surface 311 between the recesses 312 of the sapphire substrate 310, the inclined surface of the recesses 312, and the bottom surface of the recesses 312. The AlN layer 320 is composed of AlN crystals 320a grown in the recesses 312 and AlN crystals 320b grown on the surface 311.
[0052] The AlN grown on the slope of the recess 312 is a disordered crystal having a different crystal orientation from the AlN grown on the surface 311. In addition, the AlN grown on the slope of the recess 312 and the AlN grown on the bottom surface of the recess 312 also have different crystal orientations from each other, so that a disordered AlN crystal 320a is formed in the recess 312 as a result.
[0053] On the other hand, the AlN crystal 320 b grown on the surface 311 has the same crystal orientation as the sapphire substrate 310 , and there is a height difference between the surface 311 and the recess 312 , so that the AlN crystal 320 b grown on the surface 311 grows while keeping a distance from the AlN crystal 320 a grown in the recess 312 .
[0054] Depending on the growth conditions, the AlN grown on the surface 311 can also be slowly expanded in the lateral direction. By adjusting the growth conditions, the disordered AlN crystals 320a grown in the recesses 312 will not catch up with the AlN crystals 320b until the AlN grown on the adjacent surfaces 311 sandwiching the recesses 312 meet each other, thereby finally obtaining the AlN crystals 320b having a flat surface 321. When the flat surface 321 is finally obtained, since the disordered AlN crystals 320a grown in the recesses 312 do not catch up with the AlN crystals 320b grown on the surface 311, the AlN layer 320 inevitably contains voids (holes) 330.
[0055] Furthermore, in the conventional technology, when obtaining the flat surface 321 , since the expansion speed in the lateral direction during the growth of the AlN crystal 320 b is slow, it is necessary to grow a relatively thick AlN crystal 320 b of about 5 to 20 μm.
[0056] Thus, in the conventional art, when it is desired to obtain a flat surface 321, the AlN layer 320 includes pores 330 and needs to grow a thicker AlN layer 320. This is disadvantageous when the AlN layer 320 is applied to, for example, a UV-LED substrate as described below.
[0057] The UV-LED is formed by growing an n-type semiconductor layer, a light-emitting layer, and a p-type semiconductor layer on a flat surface 321 of the AlN layer 320. As a p-type semiconductor layer, it is ideal to use a p-type aluminum gallium nitride (AlGaN) layer that is transparent to ultraviolet light, but the resistance will increase excessively when a p-type AlGaN layer is used. Therefore, the current situation is to use a p-type GaN layer that absorbs ultraviolet light as at least the outermost contact layer. As a result, if you want to extract ultraviolet light from the growth surface side, most of the light will be absorbed by the p-type GaN layer. Therefore, in the current UV-LED, a structure that extracts light from the back side of the sapphire substrate is used.
[0058] According to the research of the inventors of the present application, for such a structure, since there are vacancies 330 in the AlN layer 320, the average refractive index near the interface between the AlN layer 320 and the sapphire substrate 310 is reduced, so that the ultraviolet light generated by the light-emitting layer is difficult to transmit to the substrate side. That is, the AlN layer 320 containing vacancies 330 will cause the output of the UV-LED to decrease, which is disadvantageous. In addition, the AlN layer 320 must be grown thick, which is disadvantageous from the perspective of reducing the manufacturing cost of the UV-LED.
[0059] Next, an experimental example of the present embodiment is described. In this experimental example, as the substrate 10 (sapphire substrate), a substrate with a diameter of 2 inches in which conical protrusions 12 are arranged in a regular triangular lattice is used. The height H12, the width W12 of the inclined surface, and the pitch P12 of the protrusion 12 are set to 220nm, 250nm, and 600nm, respectively. The growth conditions of the layer 20 (AlN layer) are the growth conditions exemplified above. The layer 20 is grown in a manner such that the thickness T20 from the valley 13 of the base surface 11 of the substrate 10 to the surface 21 of the layer 20 is 700nm.
[0060] Figure 3 and Figure 4 The results of this experimental example are shown. Figure 3 It is a top view image showing the result of this experimental example. Figure 3 The upper part is an image of a 5 μm square area of the surface of the AlN layer using an atomic force microscope (AFM). Figure 3 The left and right parts of the lower part are optical microscope images of the surface of the AlN layer. From the AFM image, it can be seen that the surface of the AlN layer has a step-terrace structure and is flat. In this step-terrace structure, it is estimated that the height of each step is equivalent to one or two molecules of AlN. The RMS value of the surface roughness determined by the AFM measurement is 1.6nm in this case. As a result of investigating the entire 2-inch wafer at a spacing of 10mm, the RMS value at all points is also less than 3nm. It can also be seen from the optical microscope image that the surface of the AlN layer is flat.
[0061] The AlN layer produced in this experimental example was subjected to XRC measurement at the center of a 2-inch wafer. The half-width of the (0002) diffraction was 260 seconds, and the half-width of the (10-12) diffraction was 300 seconds. The results of the investigation of the entire 2-inch wafer at every 10 mm interval showed that the half-width of the (0002) diffraction at all points was also less than 300 seconds, and the half-width of the (10-12) diffraction was less than 500 seconds.
[0062] Figure 4 The cross-sectional scanning electron microscope (SEM) image showing the results of this experimental example. Figure 2 The plane perpendicular to the arrow P12 (the M plane of sapphire and the A plane of AlN), that is, the plane orthogonal to the surface of the AlN layer. Due to the influence of charging during photography, it looks slightly different from the actual size. However, it can be clearly seen from the cross-sectional image that a flat AlN layer is formed on the surface, and the crystals constituting the AlN layer do not contain pores. It should be noted that when the cross section is observed over a wide range, it can also be observed that there are very sparsely formed pores. However, this is caused by the unevenness caused by the incompleteness of the pattern processing in the sapphire substrate, and is not an essential pore.
[0063] The amount of pores contained in the AlN layer can be estimated, for example, as follows. In a cross-sectional SEM image at a low magnification (a magnification at which a region with a width of 10 μm or more can be observed), in the AlN layer, a line L with a length of 10 μm or more parallel to the surface is drawn so that the length of the line L crossing the pores is the maximum, and the ratio of the length of the pores (the length of the line L crossing the pores) to the length of the line L is called the pore content. The amount of pores contained in the AlN layer can be estimated, for example, by such a pore content. When the pore content is less than 10%, it is defined as the AlN layer being substantially free of pores.
[0064] In this experimental example, the pore content is less than 10%, less than 5% in most cases, and 0% in the best case. That is, the AlN layer obtained in this experimental example does not contain pores substantially. The pore content is preferably less than 5%, more preferably less than 2%, and further preferably 0% (less than 0.5%).
[0065] It should be noted that Figure 7 (b) conceptually illustrates a line L drawn for estimating the pore content of the AlN layer 320 in the prior art. The pore content of the AlN layer 320 in the prior art is higher than 10%.
[0066] As described above, according to the present embodiment, a stacked member 100 can be obtained, which has a layer 20 having a flat surface 21 and grown in a manner that substantially does not contain pores on the base surface 11 of the substrate 10 on which the protrusions 12 are periodically arranged. The flat surface 21 can be obtained by growth, that is, in the form of a directly grown surface. As a result, there is no need for processing to flatten the surface 21, so damage to the AlN crystal caused by the processing can be prevented. Therefore, for example, when a group III nitride layer is further grown on the surface 21 of the layer 20, the group III nitride layer can be grown with high crystallinity.
[0067] The layer 20 is a single-layer AlN layer, that is, can be grown through a single growth step. Therefore, the layer 20 can be easily formed compared to a multi-layer AlN layer that requires multiple growth steps.
[0068] The height H12 of the protrusion 12 of the substrate 10 is 500 nm or less, and the thickness T20 of the layer 20 can be as thin as 800 nm or less as described above. Therefore, the layer 20 is easily formed in the form of a high-quality AlN layer without cracks. In addition, the layer 20 of this embodiment has a film thickness that is extremely thin compared to the AlN layer (e.g., a thickness of 5 to 20 μm) of the prior art, and therefore has the advantage of being able to significantly reduce the cost required for growth.
[0069] The stacked structure 100 can be used, for example, to produce an LED by further growing a group III nitride layer on the surface 21 of the layer 20. By making the layer 20 substantially free of pores, when the stacked structure 100 is applied to, for example, a base of an LED, the output reduction caused by the pores can be suppressed as described below. It should be noted that the stacked structure 100 can also be used for any other purpose.
[0070] Next, as an application example, a UV-LED 200 (hereinafter also referred to as LED 200 ) will be described as a light-emitting device including the laminated structure 100 . Figure 5 2 is a schematic cross-sectional view of LED 200 . LED 200 includes stacked member 100 , light emitting structure 205 disposed on surface 21 of layer 20 and composed of stacked group III nitride semiconductor layers, and n-side electrode 240 and p-side electrode 250 for passing current through light emitting structure 205 .
[0071] As the light emitting structure 205, various structures can be used as needed. The light emitting structure 205 includes, for example, an n-type semiconductor layer 210 formed on the surface 21 of the layer 20, a light emitting layer 220 formed on the n-type semiconductor layer 210, and a p-type semiconductor layer 230 formed on the light emitting layer 220. It should be noted that the light emitting structure 205 may include a strain relaxation layer between the AlN layer 20 and the n-type semiconductor layer 210 as needed.
[0072] As the strain relaxation layer, for example, a composition gradient layer can be formed, and in addition, for example, a superlattice layer can be formed. As the n-type semiconductor layer 210, for example, an n-type AlGaN layer can be formed. As the light-emitting layer 220, for example, a multi-quantum well layer formed by alternating stacks of AlGaN layers with different Al compositions can be formed. As the p-type semiconductor layer 230, for example, a stack of an electron blocking layer composed of p-type AlGaN with a high Al composition, a p-type AlGaN layer, and a p-type GaN contact layer can be formed. Each AlGaN layer has an Al composition that is transparent to the emission wavelength. The layers constituting the light-emitting structure 205 are formed by, for example, MOCVD.
[0073] An n-side electrode 240 and a p-side electrode 250 are formed on the n-type semiconductor layer 210 and the p-type semiconductor layer 230 of the light emitting structure 205, respectively. A Ti / Al electrode or the like is used as the n-side electrode 240. A Ni / Au electrode, a Ni / Al electrode, a Rh electrode or the like is used as the p-side electrode 250.
[0074] Ultraviolet (UV) light 260 (hereinafter also referred to as light 260 ) emitted from the light emitting layer 220 is extracted to the outside from the back side of the substrate 10 . Figure 5 Some paths of light 260 are illustrated. Light 260 emitted from the light emitting layer 220 and vertically incident on the flat valley portion 13 of the substrate 10 travels straight as it is, and is taken out from the back side of the substrate 10 to the outside. Light 260 emitted from the light emitting layer 220 and obliquely incident on the inclined surface of the convex portion 12 of the substrate 10 is refracted by the inclined surface, and is taken out from the back side of the substrate 10 to the outside.
[0075] By making the layer 20 substantially free of pores, it is possible to suppress the decrease in the average refractive index near the interface between the layer 20 and the substrate 10 caused by the pores. As a result, the light 260 emitted by the light-emitting layer 220 is easily transmitted to the substrate 10 side, so it is possible to suppress the decrease in the output of the LED 200 caused by the pores. It should be noted that by making the substrate 10 have the convex portion 12, compared with the case where the entire surface of the base surface 11 of the substrate 10 is flat, the component of the light 260 that is totally reflected by the base surface 11 and not transmitted to the substrate 10 side is reduced, thereby improving the light extraction efficiency.
[0076] <Other Implementation Methods>
[0077] The present invention is not limited to the above-described embodiments, and various modifications can be made without departing from the gist of the present invention. In addition, various embodiments can be appropriately combined.
[0078] In the above embodiment, a substrate having a conical convex portion 12 is exemplified as the substrate 10 for growing the layer 20, but the convex portion 12 is not limited to a conical shape. In addition, in the above embodiment, an embodiment in which the convex portion 12 is periodically arranged in two dimensions is exemplified, but the periodic arrangement of the convex portion 12 is not limited to two dimensions. Figure 6 The schematic plan view of the substrate 10 is shown as an example in which ridge-shaped protrusions 12 are arranged one-dimensionally periodically so that the extending directions of the ridges are parallel to each other. The solid lines and dotted lines extending in the vertical direction of the paper represent the ridge lines and valley lines of the protrusions 12, respectively.
[0079] <Preferred Mode of the Invention>
[0080] Preferred embodiments of the present invention are described below.
[0081] (Note 1)
[0082] An aluminum nitride laminated component comprising:
[0083] A sapphire substrate having a base surface on which projections having a height of 500 nm or less are periodically arranged; and
[0084] The aluminum nitride layer is grown on the aforementioned base surface, has a flat surface, and substantially contains no pores.
[0085] (Note 2)
[0086] The aluminum nitride laminated structure according to Supplementary Note 1, wherein the surface has a surface roughness of 3 nm or less in terms of a root mean square value determined by atomic force microscopy through a 5 μm square region of the surface.
[0087] (Note 3)
[0088] An aluminum nitride laminated structure according to Note 1 or 2, wherein the pore content is less than 10%, preferably less than 5%, more preferably less than 2%, and further preferably 0% (less than 0.5%), and the pore content is: in a cross-sectional observation image of the aluminum nitride layer (orthogonal to the surface), when a line with a length of more than 10 μm parallel to the surface is drawn so that the length of the line crossing the pore is maximized, the ratio of the length of the pore (the length of the line crossing the pore) to the length of the line.
[0089] (Note 4)
[0090] The aluminum nitride laminated structure according to any one of Supplementary Notes 1 to 3, wherein the surface has a single crystal orientation, and a low-index crystal plane closest to the surface is a +c plane of aluminum nitride constituting the aluminum nitride layer.
[0091] (Note 5)
[0092] The aluminum nitride laminated structure according to any one of Supplementary Notes 1 to 4, wherein the surface has a step-terrace structure.
[0093] (Note 6)
[0094] The aluminum nitride laminated structure according to any one of Supplementary Notes 1 to 5, wherein the half width of (0002) diffraction of the aluminum nitride layer measured by an X-ray rocking curve is 300 seconds or less.
[0095] (Note 7)
[0096] The aluminum nitride laminated structure according to any one of Supplementary Notes 1 to 6, wherein the aluminum nitride layer has a half width of (10-12) diffraction based on X-ray rocking curve measurement of 500 seconds or less.
[0097] (Note 8)
[0098] An aluminum nitride stacked structure according to any one of Notes 1 to 7, wherein the aforementioned surface is a surface on which other aluminum nitride layers can be grown in the following manner: when other aluminum nitride layers are homoepitaxially grown on the aforementioned surface, an increase in the half-width of the (0002) diffraction (or (10-12) diffraction) of the aluminum nitride constituting the aforementioned other aluminum nitride layer based on an X-ray rocking curve relative to the half-width of the (0002) diffraction (or (10-12) diffraction) of the aluminum nitride constituting the aforementioned aluminum nitride layer based on an X-ray rocking curve is less than 100 seconds.
[0099] (Note 9)
[0100] The aluminum nitride laminated structure according to any one of appendices 1 to 8, wherein the aluminum nitride layer is composed of a single aluminum nitride layer, and the single aluminum nitride layer does not have an interface where the oxygen concentration changes stepwise at a position midway in the thickness direction.
[0101] (Note 10)
[0102] The aluminum nitride laminated structure according to any one of Appendixes 1 to 9, wherein a thickness of the aluminum nitride layer from the lower end of the protrusion to the surface is 800 nm or less.
[0103] (Note 11)
[0104] The aluminum nitride laminated structure according to any one of Supplementary Notes 1 to 10, wherein a height direction of the protrusion is parallel to a c-axis direction of sapphire constituting the sapphire substrate.
[0105] (Note 12)
[0106] The aluminum nitride laminated structure according to any one of Appendixes 1 to 11, wherein each of the convex portions is cone-shaped or ridge-shaped, and a width of a slope of each of the convex portions in a plan view is 500 nm or less.
[0107] (Note 13)
[0108] The aluminum nitride laminate structure according to any one of Supplementary Notes 1 to 12, wherein a distance between the most adjacent protrusions is 1000 nm or less.
[0109] (Note 14)
[0110] A light emitting device comprising the aluminum nitride laminate structure according to any one of Supplementary Notes 1 to 13.
[0111] (Note 15)
[0112] The light-emitting device according to Supplementary Note 14, comprising a light-emitting structure which is arranged on the surface of the aluminum nitride layer and is composed of a stack of group III nitride semiconductor layers,
[0113] Light is extracted from the back side of the sapphire substrate.
Claims
1. An aluminum nitride laminated component comprising: A sapphire substrate having a base surface on which protrusions having a height of 50 nm or more and 500 nm or less are periodically arranged; and an aluminum nitride layer grown on the substrate surface, the surface of which has a surface roughness of 3 nm or less in terms of a root mean square value determined by atomic force microscopy through a 5 μm square area of the surface, The pore content of the aluminum nitride layer is 10% or less, and the pore content is: in the cross-sectional observation image of the aluminum nitride layer, when a line with a length of 10 μm or more is drawn parallel to the surface so that the length of the line crossing the pores is maximized, the ratio of the length of the pores to the length of the line, The height direction of the protrusion is parallel to the c-axis direction of sapphire constituting the sapphire substrate.
2. The aluminum nitride laminate structure according to claim 1, wherein: The surface has a single crystal orientation, and the lowest-index crystal plane closest to the surface is the +c plane of aluminum nitride constituting the aluminum nitride layer.
3. The aluminum nitride laminated structure according to claim 1 or 2, wherein: The surface has a step-terrace structure.
4. The aluminum nitride laminated structure according to claim 1 or 2, wherein: The aluminum nitride layer has a half width of (0002) diffraction measured by an X-ray rocking curve of 300 seconds or less.
5. The aluminum nitride laminate structure according to claim 1 or 2, wherein: The aluminum nitride layer has a half width of (10-12) diffraction measured by an X-ray rocking curve of 500 seconds or less.
6. The aluminum nitride laminated structure according to claim 1 or 2, wherein: The surface is a surface on which another aluminum nitride layer can be grown in the following manner: when another aluminum nitride layer is homoepitaxially grown on the surface, an increase in the half-width of the (0002) diffraction of the aluminum nitride constituting the other aluminum nitride layer measured based on the X-ray rocking curve relative to the half-width of the (0002) diffraction of the aluminum nitride constituting the aluminum nitride layer measured based on the X-ray rocking curve is less than 100 seconds.
7. The aluminum nitride laminated structure according to claim 1 or 2, wherein: The aluminum nitride layer is composed of a single aluminum nitride layer, and the single aluminum nitride layer does not have an interface where the oxygen concentration changes in a step-like manner at a position midway in the thickness direction.
8. The aluminum nitride laminated structure according to claim 1 or 2, wherein: The aluminum nitride layer has a thickness from the lower end of the protrusion to the surface of 800 nm or less.
9. The aluminum nitride laminated structure according to claim 1 or 2, wherein: Each of the convex portions is cone-shaped or ridge-shaped, and a width of a slope of each of the convex portions in a plan view is 500 nm or less.
10. The aluminum nitride laminated structure according to claim 1 or 2, wherein: The distance between the most adjacent protrusions is 1000 nm or less. 11 . A light emitting device comprising the aluminum nitride laminate structure according to claim 1 .
12. The light emitting device according to claim 11, comprising a light emitting structure which is arranged on the surface of the aluminum nitride layer and is composed of a stack of group III nitride semiconductor layers, Light is extracted from the back side of the sapphire substrate.
